The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/21683603.2018.1551819
|View full text |Cite
|
Sign up to set email alerts
|

Conduct problems, schoolwork difficulties, and being bullied: A follow-up among Finnish adolescents

Abstract: Continual conduct problems from adolescence to adulthood comprise a societal concern. Knowledge of school-related triggers and contributors to persistent conduct problems is important but still limited. We explored the role of schoolwork difficulties and being bullied by peers at school in the development of conduct problems, controlling for vulnerability factors of low cognitive competence and low prosociality. The data covered two measuring points on a longitudinal cohort of Finnish students between the ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…The latest accepted application was used to place the student. Some students had participated in the survey of the same cohorts in 2016 [ 26 ]. If a student was found in a different track than the registry placement showed and had not reapplied after 2016, the participant’s placement was revised (2011, N = 91; 2014, N = 85).…”
Section: Methodsmentioning
confidence: 99%
“…The latest accepted application was used to place the student. Some students had participated in the survey of the same cohorts in 2016 [ 26 ]. If a student was found in a different track than the registry placement showed and had not reapplied after 2016, the participant’s placement was revised (2011, N = 91; 2014, N = 85).…”
Section: Methodsmentioning
confidence: 99%
“…Parents' reports depict a higher prevalence of conduct, hyperactivity and peer problems than teachers' reports. Di culties in school may become conduct problems resulting in characteristics such as stealing, physical violence, rebellion, and bullying behaviours(Minkkinen, Hotulainen, Kinnunen, & Rimpela, 2018). Parents and teachers report has shown that adolescents with Attention De cit Hyperactivity Disorder often have an academic impairment(Sibley, Altszuler, Morrow, & Merrill, 2014).…”
mentioning
confidence: 99%